2001
DOI: 10.1007/bf03320986
|View full text |Cite
|
Sign up to set email alerts
|

Riemann-Hilbert Analysis for Laguerre Polynomials with Large Negative Parameter

Abstract: Abstract. We study the asymptotic behavior of Laguerre polynomials L (αn) n (nz) as n → ∞, where α n is a sequence of negative parameters such that −α n /n tends to a limit A > 1 as n → ∞. These polynomials satisfy a non-hermitian orthogonality on certain contours in the complex plane. This fact allows the formulation of a Riemann-Hilbert problem whose solution is given in terms of these Laguerre polynomials. The asymptotic analysis of the Riemann-Hilbert problem is carried out by the steepest descent method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(98 citation statements)
references
References 35 publications
6
92
0
Order By: Relevance
“…In [27], the leading term of the asymptotic expansion was obtained for α = −An, where A > 1. We consider a somewhat more general situation, α = −An − A 1 , where A 1 ∈ R, and using Theorem 1 we obtain more exact asymptotic formulae.…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [27], the leading term of the asymptotic expansion was obtained for α = −An, where A > 1. We consider a somewhat more general situation, α = −An − A 1 , where A 1 ∈ R, and using Theorem 1 we obtain more exact asymptotic formulae.…”
Section: Examplesmentioning
confidence: 99%
“…In [27] it is shown that Σ = Γ ∪ Σ 1 ∪ Σ 2 , where Γ is an arc that connects In [27] it is shown that the support of the equilibrium measure in the field…”
mentioning
confidence: 99%
“…The proof is rather routine, and we give only a brief version of it. For details, see [9] or [10]. Y (z) obviously satisfies the condition in (Y a ).…”
Section: Theorem 1 the Unique Solution To The Above Rhp For Y Is Givmentioning
confidence: 99%
“…Thus, the final result usually consists of a set of asymptotic expansions, each valid in a different region; cf. [3] and [10]. In this paper, we shall present a modification of this method, and construct an asymptotic expansion for P (α n ,β n ) n (z), which holds uniformly in the upper half-plane C + = {z ∈ C : Im z ≥ 0}, where α n and β n are given in (1.2).…”
Section: Introductionmentioning
confidence: 99%
“…This technique originated with Deift and Zhou [15] and was applied to the asymptotics of orthogonal polynomials by Deift et al [12,13,14]. See also [7,8,4,20,21,22,23,24] for recent developments. The Riemann-Hilbert problem for multiple orthogonal polynomials was given by Van Assche et al [39].…”
Section: )mentioning
confidence: 99%